Incontinence of the void : economico-philosophical spandrels - Žižek, Slavoj (Short circuits, 2017)
The ""formidably brilliant"" Zizek considers sexuality, ontology, subjectivity, and Marxian critiques of political economy by way of Lacanian psychoanalysis.